Chemical control of pathogens and the physiological performance of peanut seeds - Barbosa, Rafael Marani [UNESP]; dos Santos, Juliana Faria [UNESP]; Lopes, Magnólia de Mendonça [UNESP]; Panizzi, Rita de Cássia [UNESP]; Vieira, Roberval Daiton [UNESP] (My University, 2013)
The establishment of a peanut crop may be unsatisfactory due to poor seed performance in the field and among the factors attributed to this are a reduction in seed vigor during storage and the presence of pathogens. The objective of this study was to evaluate the efficiency of treating peanut seeds with fungicides and the effect on physiological performance and disease control during storage. In a completely random experimental design, two seed batches of the Runner IAC 886 peanut cultivar were submitted to five fungicide treatments (1 control - untreated; 2 thiram; 3 carbendazim + thiram; 4 fludioxonil + metalaxyl-m; 5 fludioxonil + mefenoxam + thiabendazole) and evaluated after zero, 30 and 60 days of storage. The seeds were stored untreated but treated before the evaluation of physiological performance from germination, vigor (first germination count and accelerated aging), field seedling emergence and seed sanitation tests. The results showed differences in batch performance potential during storage, with batch 1 being superior. The sanitation test showed that all the chemical seed treatments controlled pathogens efficiently (Aspergillus spp. and Penicillium sp.), but only thiram did not affect peanut seed performance in the laboratory evaluations.
Keywords: Arachis hypogaea L.; Fungicides; Germination; Seed pathology; Vigor; carbendazim; fludioxonil; fungicide; mefenoxam; metalaxyl; thiram; tiabendazole; unclassified drug; Aspergillus; controlled study; crop; germination; microbial pest control; nonhuman; peanut; Penicillium; plant physiology; plant water content; sanitation; seedling emergence